Recognition of Connective Tissue Disease-Related Interstitial Pneumonia Based on Histological Score—A Validation Study of an Online Diagnostic Decision Support Tool - Mutsumi Ozasa; Yoshiaki Zaizen; Kazuhiro Tabata; Kensuke Kataoka; Shuntaro Sato; Andrey Bychkov; Noriho Sakamoto; Hiroshi Mukae; Yasuhiro Kondoh; Junya Fukuoka (Diagnostics, 2021)
Objectives: to evaluate the number of cases of idiopathic pulmonary fibrosis (IPF) that included histological features of connective tissue disease (CTD) and to check whether they demonstrated the clinical features of CTD, using a previously reported CTD-interstitial pneumonia (IP) index that histologically differentiates CTD-associated and idiopathic IP. Methods: patients diagnosed with IPF following video-assisted thoracoscopic biopsy through multidisciplinary team diagnosis between 2014 and 2017 were selected. Pathological observation was made by four pathologists who scored eight observational items needed for the CTD-IP index. Cases determined as CTD, by the CTD-IP index, were extracted, and their clinical features were compared. Results: a total of 94 cases of IPF were identified, of which 20 were classified into the CTD group using the CTD-IP index with reasonable interobserver agreement (k = 0.76). Cases pathologically classified into the CTD group were significantly associated with female sex, non-smoking history, autoantibody positivity, and CTD symptoms (p = 0.01, 0.03, 0.01, and 0.04, respectively). Conclusions: patients with IPF with pathological findings of CTD showed clinical characteristics similar to those of patients with CTD.